Bivalves and quartz crystals in Miocene clastics near Dobrina in Haloze, Slovenia - Mikuž, Vasja; Žorž, Mirjan (Geologija, 2004)
Described are Miocene bivalves of species Megacardita jouanneti (Basterot, 1825) and quartz crystals of the »rocks crystal« variety. Both were found in clastics - quartz conglomerates and sandstones at Dobrina in Haloze. Until recently in rocks from this area no fossil remains were known. Also the well shaped quartz crystals of moderate sizes and various inclusions are new for Slovenia.